Analisis Niat Penggunaan Knowledge Management System pada Perusahaan Pupuk di Indonesia - Feby Artwodini Muqtadiroh; Amna Shifia Nisafani; Muchammad Wijdan Alyosa (Jurnal Teknosains, 2019)
PT ABC is one of the state-owned companies and one of the fertilizer producers in Indonesia. At present PT ABC has implemented a Knowledge Management System (KMS) in Human Resources Department. KMS serves as a tool for employees to consult in various fields regarding knowledge sharing, as a source of information and administration processes for payroll, leave, pensions and others. However, the existence of KMS is unable to guarantee the employees feel helped, for example, old employees who do not understand technology will have difficulty running KMS and some employees are not accustomed to dealing with information technology because they are used to consulting with humans. To measure the level of KMS acceptance for employees at PT ABC, this research uses the Chorng-Shyong Ong model which is a Technology Acceptance Model (TAM) model by utilizing the Power Issues.The purpose of this study was to find out the level of KMS acceptance in PT ABC based on the perspective of employees by identifying the basic factors, which affect cognitively and affectively to increase the internal beliefs, attitudes, and employee intention to use KMS through the recommendations given for the system improvement. And the results of this study indicate that the factors of perception to the usefulness, perceived ease of use, and the influences of others positively influence the intention to use KMS in PT ABC. There are only 3 of 7 hypotheses were accepted in accordance with the conditions that exist in PT ABC for the implementation of KMS. Of the 3 hypotheses accepted, the recommendations for improvement are derived based on the employee's suggestion in open questionnaires.